Bentuk-Bentuk Dukungan Keluarga Terhadap Ibu dengan HIV Positif dalam Kepatuhan Terapi ARV di Kota Semarang - Nurina Dyah Larasati; Zahroh Shaluhiyah; Antono Suryoputro (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2015)
ABSTRACTForms of Family Support to Mothers With HIV Positive in Compliance With ARV Therapy in The City of Semarang; HIV cases among housewives is increasing from year to year. Data in September 2012 showed that housewife was ranked 2. Family support is needed to mothers with HIV positive in living her life with a dual role as a wife and mother as well as in compliance with ARV. This study aims to explore the opinion of mothers with HIV positive in terms of family support in ARV therapy adherence in Semarang. This study uses a qualitative research approach. Informants selected by purposive sampling with the help of key informants that case manager of KDS Arjuna Plus The Data validity which used with source triangulation method such family informant and case manager.The results of this study showed that family support from husbands, parents, and children like to remind to take medicine, listening to complaints from informants, drove to the clinic to support financially can improve informants adherence in compliance with ARV therapy. Compliance informants in ARV therapy has increased from time to time with an awareness of the informants and family and social support.Keywords : Mothers with HIV positive, Family support, Compliance